2020
DOI: 10.1016/j.icarus.2019.113523
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between dust devil radii and heights

Abstract: The influence of dust devils on the martian atmosphere depends on their capacity to loft dust, which depends on their wind profiles and footprint on the martian surface, i.e., on their radii, R. Previous work suggests the wind profile depends on a devil's thermodynamic efficiency, which scales with its height, h. However, the precise mechanisms that set a dust devil's radius have remained unclear. Combining previous work with simple assumptions about angular momentum conservation in dust devils predicts that R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(38 reference statements)
2
5
0
Order By: Relevance
“…DDA increases, in part, as the boundary layer deepens, which likely results in taller dust devils. Jackson (2020) suggested that taller dust devils ought to have larger dust densities, and the results here comport with that prediction.…”
Section: What Fraction Of Encountered Vortices Are True Dustsupporting
confidence: 89%
“…DDA increases, in part, as the boundary layer deepens, which likely results in taller dust devils. Jackson (2020) suggested that taller dust devils ought to have larger dust densities, and the results here comport with that prediction.…”
Section: What Fraction Of Encountered Vortices Are True Dustsupporting
confidence: 89%
“…DDA increases, in part, with as the boundary layer deepens, which likely results in taller dust devils. Jackson (2020) suggested that taller dust devils ought to have larger dust densities, and the results here comport with that prediction.…”
Section: What Fraction Of Encountered Vortices Are True Dust Devils?supporting
confidence: 89%
“…Indeed, there is a dearth of vortex encounters with large ∆P 0 and large radiative excursions in Figure 7(a), which seems counter-intuitive: we might expect the most vigorous vortices to lift the most dust. Theoretical expectations (Jackson 2020) and observations of martian dust devils (Greeley et al 2006) corroborate this expectation. Instead, this dearth may arise simply from the vortex encounter geometries.…”
Section: What Fraction Of Encountered Vortices Are True Dust Devils?mentioning
confidence: 59%
“…Certainly, an increased advection speed would be expected to increase the rate of dust devil encounter since more dust devils would be advected past the camera or meteorological sensor, what has been called the "advection effect". Moreover, some non-zero winds are probably necessary to provide the vorticity requisite for dust devil formation (Jackson 2020), and, in any case, turbulent winds must accompany the convectively unstable conditions that produce dust devils. However, as discussed in Rafkin et al (2016), higher wind speeds may suppress a high near-surface lapse rate and reduce the vigor of convective mixing associated with dust devils.…”
Section: Why Didn't Insight Image Any Dust Devils?mentioning
confidence: 99%